The Manifestation of Monster and the Emotional Repression in Jennifer Kent’s The Babadook (2013) - Inayatul Chusna; Anggita Rizkiarachma Ansyahputri; Avi Ainul Fikri; Muhammad Rafli (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2020)
The purpose of this research is to explore the emotional state of the main character, Amelia, in The Babadook film. The film portrays how Amelia deals with her loss and how the monster Babadook represents the repressed feeling of loss. This research analyses the emergence of the Babadook, how it affects her, and how her behaviors are considered as melancholia by using qualitative method and the theory of psychoanalysis, Mourning and Melancholia by Sigmund Freud (1917). The research finds that the eerie monster haunts Amelia whenever she is confronted to her repressed emotion: grief and self- loathing. The Babadook monster is the manifestation of grief and loss. As the monster getting stronger, the sinister presence of the Babadook starts to affect Amelia’s psyche as she is getting more paranoid and more aggressive. She is also unable to show affection toward her son. Moreover, Amelia shows an act of self-destruct by keeping herself from the outside world and unconsciously blaming herself for the death of the husband. Those behaviors indicate that Amelia comes into the state of melancholia. Finally, she manages to overcome the state by accepting the feeling of loss and let herself mourn. The study of this film suggests a way of dealing with trauma and loss by accepting their permanent presence in life.